Peran Atribut Destinasi Terhadap Pembentukan Citra Kota Bandung Sebagai Destinasi MICE di Indonesia - Raga, Marsianus (Politeknik Pariwisata NHI Bandung, 2019)
Meeting, Incentive, Conference and Exhibition/MICE business) continues to grow over time. Every country continues to strive to develop the MICE destination attributes such as affordability in terms of price/cost, tourist attractions, accessibility, amenity, activity and accountability possessed by the city. The purpose of this study was to research the response of the respondents (members of Asosiasi Perusahaan Pameran Indonesia/ASPERAPI) regarding Bandung destination attributes and image as MICE destinations and to examine the role or influence of destination attributes on forming Bandung city image as a MICE destination in Indonesia. This study uses multiple regression analysis to test the first classical assumption, the next multiple regression analysis which includes T test and F test analysis to examine the spatial relationship each variables of attributes destination to image variable and simultaneous relationship between destination attributes variable with image variable. The results of descriptive data processing, the destination attributes and the image ofthe city of Bandung in good category. The results ofT test and F test showed that the affordability and activity have no significant effect on forming the image Bandung city as MICE destination. All attributes simultaneously effect on forming image of Bandung city as a MICE destination. The influence of destination attributes variable on forming image ofthe city of Bandung was 88.4%, while the remaining11.6% is influenced by other factors not observed. The availability of destination attributes with the best quality and quantity in Bandung will enhance the image of Bandung city as a MICE destination.